Moral Guidelines for Women in Wawacan Pranata Istri ka Carogé Manuscript - Wafiq Nuraini Cumana; Agus Suherman; Dedi Koswara (Jurnal Sastra Indonesia, 2024)
The problem in this research is how morals are realized in the Wawacan Pranata Istri ka Carogé text. This research aims to describe the moral manifestations contained in the Wawacan Pranata Istri ka Carogé text. This research includes qualitative research with analytical descriptive methods. Data collection techniques were carried out using literature review techniques and data analysis using research instruments in the form of data cards. Technical data analysis is carried out in stages: a) identify data, b) analyze data, c) interpret data, and d) conclude. The results show that the moral values contained in the Wawacan Pranata Istri ka Carogé manuscript consist of 1) human morals towards God (9), including praising God, avoiding His prohibitions, and practicing the teachings of the prophet, 2) human morals towards themselves (16), including being honest, being able to control oneself, being responsible for oneself personal, and is simple, 3) human morals towards other humans (20), including having concern for others, respecting and appreciating husbands, 4) human morals towards time (1), namely respecting the time and not wasting time which is characterized by awareness of linear time, and 5) human morals in achieving inner and outer happiness (3), namely the satisfaction and happiness of Dewi Iyar in having Sultan Mahmud as her well-off husband. Apart from introducing culture, this research is intended so that the moral embodiment contained in the Wawacan Pranata Istri ka Carogé text can be used as a moral guideline in actual daily practice, especially for women living their domestic lives.